2007
DOI: 10.1021/ac061246a
|View full text |Cite
|
Sign up to set email alerts
|

Biological Imaging of HEK293 Cells Expressing PLCγ1 Using Surface-Enhanced Raman Microscopy

Abstract: Surface-enhanced Raman scattering (SERS) imaging has been used for the targeting and imaging of specific cancer markers in live cells. For this purpose, Au/Ag core-shell nanoparticles, conjugated with monoclonal antibodies, were prepared. The procedures to label live cells with those bimetallic nanoprobes have been developed and used for highly sensitive SERS imaging of live cells. In the present study, live HEK293 cells expressing PLCgamma1 have been used as the optical imaging target. Our results demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
171
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(186 citation statements)
references
References 29 publications
(36 reference statements)
3
171
0
Order By: Relevance
“…Roughened surface noble metal nanoparticles labeled with binding affinity molecules have also been shown to dramatically increase the Raman signal of their complementary molecules once attached through the SERS mechanism (12,20,21). Conjugation of monoclonal antibodies with SERS nanoparticles for targeting and imaging of specific cancer markers in live cultured cells was also recently investigated (5). Another study presents the first in vivo application of SERS for glucose measurements in a rat (22) by s.c. implantation of functionalized SERS nanospheres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roughened surface noble metal nanoparticles labeled with binding affinity molecules have also been shown to dramatically increase the Raman signal of their complementary molecules once attached through the SERS mechanism (12,20,21). Conjugation of monoclonal antibodies with SERS nanoparticles for targeting and imaging of specific cancer markers in live cultured cells was also recently investigated (5). Another study presents the first in vivo application of SERS for glucose measurements in a rat (22) by s.c. implantation of functionalized SERS nanospheres.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence imaging, in particular, has significant potential for in vivo studies but is limited by several factors (5,6), including a limited number of fluorescent molecular imaging agents available in the near infra-red (NIR) window with large spectral overlap between them, which restricts the ability to interrogate multiple targets simultaneously (multiplexing). In addition, background autofluorescence emanating from superficial tissue layers restricts the sensitivity and the depth to which fluorescence imaging can be used.…”
mentioning
confidence: 99%
“…SERS targeted measurement and identification of several types of cancer cell has been shown, including osteosarcoma cells using AuNP SERS [303], cancerous renal cell detection [304], and Ag/Au core-shell nanoparticles conjugated with antibodies were used to image PLCγ protein in HEK293 cells [305]. Targeted SERS detection of circulating tumor cells has been shown in the presence of white blood cells [306].…”
Section: Applicationsmentioning
confidence: 99%
“…However, Ag is considered unstable, degrades in vivo and is typically synthesized with cetrimonium bromide (CTAB), which is considered cytotoxic [282][283][284]. Additionally, it has been demonstrated that the peak intensity ratios of the Raman signal change significantly when silver aggregates are used leading to inconsistent results and poor reproducibility [276,[285][286][287].…”
Section: Surface Enhanced Raman Scattering (Sers) and Electromagneticmentioning
confidence: 99%